COVID-19 vaccine hesitancy in Spain and associated factors - Maria Falcon; Carmen Rodríguez-Blázquez; María Romay-Barja; María Romay-Barja; Alba Ayala; Alba Ayala; Alfredo Burgos; María José De Tena-Dávila; Maria João Forjaz; Maria João Forjaz (Frontiers Media S.A., 2023)
IntroductionThe present study explores the reasons of those who have not been vaccinated in the later stage of the vaccine rollout in Spain and its associated determinants.MethodsCluster and logistic regression analyses were used to assess differences in claimed reasons for vaccine hesitancy in Spain using two samples of unvaccinated people (18-40 years old) gathered by an online cross-sectional survey from social networks (n = 910) and from a representative panel (n = 963) in October-November 2021.ResultsThe main reasons for not being vaccinated were believing that the COVID-19 vaccines had been developed too fast, they were experimental, and they were not safe, endorsed by 68.7% participants in the social network sample and 55.4% in the panel sample. The cluster analysis classified the participants into two groups. Logistic regression showed that Cluster 2 (individuals who reported structural constraints and health-related reasons such as pregnancy or medical recommendation) presented a lower trust in information from health professionals, had a lower willingness to get vaccinated in the future, and avoided less social/family events than those in Cluster 1 (reasons centered in distrust on COVID-19 vaccines, conspiracy thoughts and complacency).ConclusionsIt is important to promote information campaigns that provide reliable information and fight fake news and myths. Future vaccination intention differs in both clusters, so these results are important for developing strategies target to increase vaccination uptake for those who do not reject the COVID-19 vaccine completely.